HUBUNGAN DEPRESI DAN PERILAKU KONFORMITAS DENGAN KEJADIAN INTERNET GAMING DISORDER PADA REMAJA - Muchlis, Akmalia (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2024)
Internet gaming disorder is a phenomenon that causes quite a bad impact. Several influencing factors are internal factors, situational factors, external factors, and social factors. Regarding situational factors, a person often uses online games to make himself comfortable when his psychology is bad. While regarding social factors in adolescence, a person wants to be liked and tends to change his opinion or behavior to be accepted by his group. The purpose of this research is to find out the relationship between depression and conformity behavior toward internet gaming disorder in adolescents. The study was conducted with a population of students from the Faculty of Medicine, the University of Muhammadiyah Semarang with a sample of 85. The study was conducted using the IGDS9-SF, PHQ-9, and Conformity Questionnaires. From the data obtained, a correlation test was carried out. The study's results found a significant relationship between depression and conformity behavior with internet gaming disorder. The depressive state has moderate or strong strength and is positive linear. Meanwhile, conformity behavior has a low or relatively weak relationship strength and is negatively linear. The results of this study can help identify factors related to internet gaming disorder so that this can be minimized.